Pemanfaatan Teknologi dalam Penulisan Parafrase Tulisan Ilmiah - Runi, Runimeirati; Fadilah, Nur; Risal, Andi Alviadi Nur (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2025)
Technological advances have had a significant impact on various aspects of research and scientific writing, including the paraphrasing process. Paraphrasing is an important technique in academics to convey information from other sources in a different language without changing the original meaning. Artificial intelligence (AI) and natural language processing (NLP)-based technologies have introduced various automatic paraphrasing tools that help writers improve originality and avoid plagiarism. This article discusses various types of paraphrasing technology, their benefits in academia, and the challenges faced in their use. The results of the study show that the use of paraphrasing technology can improve efficiency and accuracy in scientific writing, but still requires human evaluation to ensure academic quality and integrity. With the right use of technology, paraphrasing in scientific writing can be more effective and ethical.